Membangun Ketahanan Psikologis Pasangan Muda Melalui Konseling Berbasis ABS-SBK Mengantisipasi Perceraian - Irman, Irman; Silvianetri, Silvianetri; Zubaidah, Zubaidah; Yeni, Putri; Hertasmaldi, Hertasmaldi; Mardianto, Mardianto (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The dynamics of early divorce become a social problem that has an effect on the destruction of the family life level. This phenomenon requires empowerment from various elements, especially in the field of family counseling, so that married couples can live happily in building a sakinah mawah family. The purpose of this service is to build psychological resilience for young couples through ABS-SBK-based counseling. The approach uses participatory action research, with a research process that is carried out in a systematic, collaborative and sustainable manner for social transformation. The service background is in Lintau Buo, Tanah Datar Regency, with the target being young couples. The result of this dedication is the change in the perspective of young couples about the purpose and nature of marriage, the emergence of an increase in psychological resilience in responding to the problems of domestic life. It is recommended to the local government, especially in Tanah Datar, to oblige couples to attend premarital counseling before marriage.Dinamika perceraian dini menjadi persoalan social yang berefek pada rusaknya tataran kehidupan keluarga. Fenomena ini membutuhkan suatu pemberdayaan dari berbagai elemen khususnya bidang konseling keluarga, agar pasangan yang menikah dapat hidup bahagia dalam membangun keluarga sakinah mawah. Tujuan pengabdian ini, membangun ketahanan psikologis pasangan muda melalui konseling berbasis ABS-SBK. Pendekatan yang digunakan participatory action research, dengan proses riset dilaksanakan secara sistematis, kolaboratif, dan berkelanjutan untuk transformasi sosial. Adapun latar pengabdian di Lintau Buo Kabupaten Tanah Datar dengan target pengabdian adalah pasangan muda. Hasil pengabdian terjadinya perubahan cara pandang para pasangan muda tentang tujuan dan hakikat pernikahan, munculnya peningkatan ketahan psikologis dalam merespon persoalan kehidupan berumah tangga. Direkomendasikan kepada pemerintahan daerah khususnya di Tanah Datar untuk mewajibkan para pasangan mengikuti konseling pranikah sebelum dilakukan pernikahan.